STUDI KOMPARATIF HASIL BELAJAR SISWA MELALUI PEMBELAJARAN TERPADU MODEL CONNECTED BERBASIS KOOPERATIF PADA BIDANG STUDI IPA DENGAN MATERI BAHAN KIMIA DALAM MAKANAN PADA SISWA KELAS VIII SMP NEGERI 19 PALU - Timang, Rosmiati; Tangkas, I Made; Sakung, Jamaluddin (Jurnal Akademika Kimia, 2013)
This research was aimed at finding out the comparisons of students study output of Class VIII of SMP Negeri 19 Palu, done by the implementing connected model of integrated learning - based cooperative learning and conventional model. This research was quasi experiment with pre test-post test control group design. The research sample was chosen through purposive sampling technique with two classes involving experimental and control classes. Those were Class VIIIA as the experimental class while Class VIIIB as the control one, who have the same class average value. The technique of collecting data was essay test consisting of five test items. The data analysis result showed that the average of post test and pre test score difference of the control class was 4.84 while the experimental one was 10.92. The result of statistical calculation of these two classes which tested through U-Mann Whitney Test with and 95%, degree of freedom was Zcounted < Ztable (-4.594 < -1.96). It means that there were significant differences of students study output between experimental class and control one. Therefore, the integrated learning can be applied at school in order to increase the students study output and the meaningful learning of students.